Policymaker Influence on SMKN Kudu Library Development - Eka Noviyanti; Rita Mutiarni (Universitas Muhammadiyah Sidoarjo, 2023)
This qualitative study examines the impact of policymakers on the enhancement of the Kudu State Vocational High School library's performance. Primary data was gathered through in-depth interviews with key informants including the Principal, Head of Library, and Vice Principals I, II, and III, while secondary data included information and visuals of the library. The findings reveal that policymakers play a crucial role in creating a conducive physical and non-physical environment for the library. The physical infrastructure and technological resources are found to be satisfactory, while non-physical aspects prioritize staff responsibilities. A systematic monitoring system, including performance appraisals by the school principal, is in place, alongside appropriate rewards. Overall, there exists a culture of fairness, safety, and harmonious relationships between library staff, teachers, and leadership. This study highlights the instrumental role of policymakers in optimizing library facilities and management, with potential implications for educational institutions worldwide. Highlight: Policymaker Influence: This study underscores the significant impact of policymakers in shaping the performance and environment of a vocational high school library, emphasizing their crucial role in educational infrastructure development. Balanced Approach: The findings reveal a balanced focus on both physical and non-physical elements, ensuring satisfactory infrastructure and technological resources alongside prioritized staff responsibilities, reflecting a comprehensive approach to library enhancement. Systematic Monitoring and Rewards: The presence of a structured monitoring system, including performance evaluations by the school principal, and appropriate rewards, contributes to a culture of fairness, safety, and positive relationships among library staff, teachers, and leadership, fostering a conducive educational environment. Keyword: Policymakers, Vocational High School, Library Performance, Qualitative Study, Educational Institutions